STRUCTURAL-DIMENSIONAL CONCEPT OF TOURISM SERVICE QUALITY - Vujović, Vukan P. (The European Journal of Applied Economics, 2013)
The difficulties of delivering a consistently satisfactory quality of tourism services emerge as a result of the discrepancies between the productive structures and corresponding dimensional features of delivering values ​​during their cycle of consumption. Organizational enterprise system is the primary responsible for the above mentioned phenomenon, and it consists of production (working) units and departments in charge of quality management as well as control and monitoring of the production processes, that is, the flow of delivery. This paper discusses the current models of structural complexity, dimensional observations of quality as well as the phases of user participation throughout the life cycle of tourism services. The possibility of identifying several typical levels in the complex tourism product provides the groundwork for a more meaningful comparison between “projected and actual quality”, as well as achieving greater organizational performances in the domain of ​​market-delivered value of the resulting service. The main objective of this paper is to provide a theoretical basis for the implementation of deeper organizational and functional analysis models and continuous monitoring of the achieved quality. The effects of such systematic approach would be manifested to the ultimate degree of fulfillment of expectations and the overall customer or user satisfaction with tourism service.